CEO’s entrepreneurial orientation and employees’ innovative behaviour: the roles of environmental turbulence and felt responsibility - Xiaokai Li; Lijing Zhao; Shenyang Hai (Humanities & Social Sciences Communications)
Abstract This study aimed to explore the mechanisms that promote employees’ innovative behaviour (EIB). Based on social cognitive theory, a multilevel approach was used to analyse the cross-level relationships among chief executive officer (CEO) entrepreneurial orientation (EO), employees’ felt responsibility for constructive change (FRCC), and EIB, with environmental turbulence as a boundary condition. A sample of 45 CEOs and 488 employees from Chinese firms participated in the study. Multilevel modelling results indicated that CEO EO positively correlates with employees’ FRCC. Employees’ FRCC is positively correlated with EIB. CEO EO indirectly impacts EIB through employees’ FRCC. Environmental turbulence strengthens the indirect effects of CEO EO on EIB through their FRCC. By revealing this cross-level mechanism, our study broadens the scope of social cognitive theory and provides practical implications for managers by showing how CEO EO indirectly impacts EIB through employees’ FRCC, with environmental turbulence amplifying this effect.